Integration of multiscale porosities and permeabilities in Paleogene reservoir rocks of the Middle Magdalena Valley Basin, Colombia: Integración de porosidades y permeabilidades a múltiples escalas en rocas reservorio del Paleógeno en la Cuenca del Valle Medio del Magdalena, Colombia (BISTUA Revista de la Facultad de Ciencias Básicas, 2025)
This study presents a descriptive mineralogical and textural analysis of sedimentary rocks located at the top of Paleogene formations in the Middle Magdalena Valley Basin, specifically within the La Paz, Esmeralda, Colorado, and Mugrosa formations. These units exhibit clearly distinguishable sedimentary structures, depositional environments, and mineral compositions. Advanced techniques such as X-ray computed tomography (CT), petrography, X-ray diffraction (XRD), and scanning electron microscopy (SEM) were used to thoroughly characterize the sedimentological, mineralogical, and porosity properties of the samples. X-ray CT enabled the identification of sedimentary and biogenic structures, as well as syn-sedimentary deformations, and provided density and effective atomic number values that are useful for facies differentiation. Petrographic analysis revealed sandstones with variable grain sizes, typical of fluvial environments, showing significant variations in grain size, a wide range of cementing materials, and well-developed secondary porosity that enhances reservoir permeability. XRD identified quartz, feldspars, and clay minerals as the main components, while SEM highlighted the distribution of clay minerals within the pores. The observed lithologies include polymictic conglomerates, shales, sandy shales, sublithic sandstones, and lithic sandstones, associated with fluvial channels, floodplains, and meandering river systems. Computed tomography is consolidated as a key non-destructive tool in sedimentological interpretation, offering high-resolution imaging and valuable data on density, mineralogy, lithology, porosity, and facies. This multidisciplinary approach provides essential information for reservoir characterization, the reconstruction of depositional environments, and the understanding of geological history, contributing to the advancement of geological research and resource exploration in the Middle Magdalena Valley Basin.